Measuring Overall Equipment Effectiveness Of Pressure Die Casting Machine - Jiga, Elnie Carina (2019)
This project focused on measuring the Overall Equipment Effectiveness (OEE) of pressure die casting in one of the casting company in Malacca. In manufacturing environments, OEE has become the foundation in improving the business strategy since it identifies the direct and ‘hidden’ productivity and quality costs which refer to the production lost. For the past 100 years, the manufacturing sector has become an incredible contribution to the global economic growth and it has a wide acknowledgement in the area of poverty mitigation. Thus, manufacturing company needs to increase their productivity for them to survive and to attain breakthrough. Productivity is mostly affected by the losses in terms of materials, machines or equipment. Thus, implementation of OEE will help in identifying the potential losses and the process which is falling off. Besides, by using OEE, the big picture of the problem and the details surrounding the problems can be answered. The casting company in which the project is held did not have their own OEE data since, they do not know on how to implement OEE. Therefore, the aims of this project are to measure the value of Overall Equipment Effectiveness of pressure die casting machine, to analyze the problems which lead to decrease in effectiveness through Six Big Losses and to enhance the machine effectiveness through recommended solution. The scope of this project includes the five pressure die casting machine, the data for the OEE value calculation, the problem which contributes to the decreased in effectiveness and the recommended solution to countermeasure the problem. To measure the value of OEE, data are collected by using time study. These data are then calculated using OEE formula and then, compared with the world class value. Then, the problems are identified by using Pareto Chart. The problems identified from Pareto Chart are then group into the categories in Fishbone Diagram. The problems are then analyzed further using Why-Why Because Logical Analysis (WWBLA) to identify the root causes and countermeasure for the problems. From the result, it can be known that the OEE value for each pressure die casting machine is still below the world class value which is 85%. From the problems identified using Pareto Chart, it is found that the countermeasure for the problem can be concluded by making a working list for daily cleaning and maintenance. Using the working list of the daily cleaning and maintenance, the task executed can be tracked.